Grain-filling pattern of super hybrid rice Liangyoupeijiu under direct seeding and transplanting condition - Badshah, MA; Mei, Tu Nai (International Journal of Agricultural Research, Innovation and Technology, 2014)
To evaluate the grain-filling pattern, Chinese first super hybrid rice, Liangyoupeijiu was grown under tillage and establishment methods at a spacing of 20 cm × 20 cm with one seedling hill-1 and at a seeding rate of 22.5 kg ha-1 in Changsha, Hunan Province, China in 2012. Our results showed that, superior grain weight in TP had always higher than DS up to 24 DAH but at 36 DAH, grain weight had similar in both TP and DS. Middle grain weight was higher in TP than DS up to 18DAH but it was higher in DS than TP at 24 36 DAH and at 36 DAH, grain weight of DS had significantly higher than TP. Inferior grain weight was higher in TP than DS up to 12 DAH but it was higher in DS than TP at 24 -36 DAH and at 36 DAH, grain weight of DS had significantly higher than TP. Grain-filling rate of superior grain had higher in TP than DS up to 18 DAH but it was higher in DS than TP at 30 DAH. In middle grain, it was higher in TP at 6DAH but in DS, it was higher at 30 DAH. In inferior grain, it was higher in TP at 36 DAH but in DS, it was higher at 30 DAH. The heavier grain was found in TP only in superior grain but DS had heavier grain both in middle and inferior grain. Grain-filling rate of superior grain was higher in TP than DS and it was similar in both TP and DS in middle grain. But in inferior grain, it was significantly higher in DS than TP. Transplanting method produced slightly higher grain yield due to higher sink size (more number of spikelets caused by longer panicle and more number of spikelet per cm of panicle) but it was statistically similar with DS. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.20972 Int. J. Agril. Res. Innov. & Tech. 4 (1): 11-15, June, 2014